Beyond the safety value : recent trends in Caribbean migration. - DUANY, Jorge (1994)
Outlines the historical background of Caribbean emigration since the late 18th century, and identifies four main currents in Caribbean migration in the late 1980s and early 1990s, viz. emigration to the metropoles; emigration to mainland Latin American countries; migration within the region; and, return migration. Notes that for the last two hundred years, the Caribbean has exported labour in exchange for capital, but this is a temporary outlet for an excess supply of workers, not a permanent solution for persistent poverty. Concludes that (1) more than two centuries of external migration have not solved the socio-economic problems of the region, but have aggravated them; (2) the current trend toward migration to the core countries of the capitalist world economy reinforces the dependent position of the Caribbean vis-a-vis those countries; (3) the high proportion of young, skilled, and educated migrants represents a substantial loss of human capital for Caribbean societies; and, (4) the regional impact of international migration has been economically and politically problematic.